A Clinical Study on 299 Cases of Nasal Bone Fractures - Saiki, Tadahiko; Ogawa, Teruhiro; Kuroda, Kazuaki; Miyahara, Satoko; Makino, Takuma; Koyama, Takahisa; Onoda, Tomoo (International Journal of Practical Otolaryngology, 2019)
We clinically investigated 299 cases of fresh nasal bone fractures diagnosed using computed tomography (CT) scan in our hospital between January 2008 and December 2017. The ages of the patients ranged from 2 to 93 years with an average of 29.4 years. There were 207 males and 92 females. The causes of the nasal bone fractures included sports (93 cases), falls (80 cases), blow or injuries (53 cases), violence or fights (40 cases), and traffic accidents (33 cases). Males in their teenage years accounted for the majority of cases, particularly in the sports-related injuries. In these cases, the most common cause was baseball (32 cases), followed by soccer (19 cases), softball (15 cases), basketball (8 cases), and so on. In the cases of traffic accidents, nasal bone fractures were caused by bicycles (18 cases), cars (10 cases), motorcycles (2 cases), and so on. Elderly males and females accounted for high numbers of falls. The external appearance of the nasal bone fractures were divided into three types: the displacement type (171 cases), depressed type (96 cases), and mixed type (32 cases). CT scan revealed nasal septum fractures in 132 cases (44.2%). Complicated facial bone fractures, apart from nasal septum fractures, were found in 35 cases (11.7%, mainly blow-out and maxillary bone fractures). In total, 221 cases (73.9%) underwent closed reductions of the nasal bone fracture. Of these, 206 cases (93.2%) were treated under general anesthesia and in 131 cases (59.3%), open reduction of the nasal septum fractures was mainly performed. In the cases of nasal bone fractures combined with nasal septum fractures, open reduction of the nasal septum fractures was helpful for the recovery of the nasal obstruction and nasal deformity.
Keywords: clinical study; nasal bone fracture; nasal septum fracture; cause; reduction